ANALISIS KADAR RHODAMIN B PADA LIPTINT YANG BEREDAR DI PASAR SEGIRI KOTA SAMARINDA DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Hiasinta Meliana Hangin; Susana Linden; Nurillahi Febria Leswana (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Liptint is one type of cosmetic lip color that is often used by women. The use of rhodamine B as a cosmetic coloring agent is prohibited by BPOM because Rhodamine B can be carcinogenic and spur the growth of cancer cells if used continuously. The purpose of this study was to determine the presence or absence of harmful substances Rhodamine B in Liptint circulating in the market Segiri Samarinda. Liptint samples were studied as many as 10 samples. Qualitative test of rhodamine B by thin layer chromatography observed under UV lamp light 254 nm. Based on the qualitative test results, samples that tested positive for Rhodamine B were samples A, B, C, E, G, H, I, and J. sample A, B have Rf value (0,907), sample G, I and J (0,802), sample C (0,789), sample H (0,828) and sample E (0,921) and raw Rf Rhodamin B (0,921) with pink spots when viewed vusual and orange spots stain when placed under UV light 254 nm. Quantitative test results from 10 samples, 9 samples tested positive for rhodamine B, namely samples A , B, C, E, F, G, H, I and J with an average content of 0,02%-0,5% w/w.